Perancangan Sistem Informasi Absensi berbasis Web pada Toko Jaya Plastik - Zulfachmi, Zulfachmi; Zulkipli, Zulkipli; Rahmad, Abdul (Prosiding, 2024)
An activity of collecting data that is part of the reporting activity, contains attendance data that is collected and managed to determine the frequency of attendance at an activity that can be used whenever needed, interpreted as absence. It was identified that there was an ineffectiveness in the process of collecting employee attendance lists at Toko Jaya Plastik. Then, this also raises another problem, namely inaccurate information will affect the calculation of employee salaries. Thus, a web-based attendance information system is needed so that attendance activities can be accessed by employees using smartphones. Based on these problems, the researcher took the initiative to design and implement a web-based attendance system. The programs used to design the attendance system are Visual Studio Code, MySQL, XAMPP, and Google Chrome. The researcher conducted observations and interviews with Toko Jaya Plastik, to obtain information related to the attendance application system. Then, this web-based attendance information system was developed and implemented with the PHP, HTML, Java Script, CSS programming languages ​​and using the MySQL database. Based on the results of the research and system design, it can be concluded that, after testing, the designed web-based attendance system can be implemented properly. The suggestion for further research is the development of the QR Code scan feature so that it can be done for a lifetime.